Scenario for adequate cutaneous vitamin D3 synthesis due to solar radiation in Poland for people with phototype II and III - Narbutt, Joanna; Lesiak, Aleksandra; Krzyścin, Janusz; Rajewska-Więch, Bonawentura (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction. The limited outdoor activity of contemporary people results in deficiency of vitamin D. An adequate vitamin D level cannot be achieved due to random insolation. A scenario of pro-healthy outdoor behavior is needed that takes into account climatic conditions in Poland. Objective . To present the outdoor activity scenario in Poland for people with phototype II and III to get an adequate vitamin D 3 dose without the risk of erythema. Material and methods. The paper presents the results of mathematical simulations of UV doses received by persons with phototype II and III in the spring/summer season in Poland (Jastrzębia Góra, Zakopane). The following scenarios are examined: using all the time a sunscreen with SPF30, short sunbathing without photo-protection and application of a sunscreen with SPF30 for the rest of the day. Results. During late spring and summer in Poland it is possible to get a vitamin D 3 dose of 2000 IU due to solar radiation without the risk of erythema. For persons with phototype II and III short (20–30 min) near-noon exposure without photo-protection then application of sunscreen with SPF30 for the rest of the time spent outdoors is recommended. Clothing should allow insolation of at least 1/4 of the whole skin area. Conclusions . Avoiding near-noon solar radiation or using sunscreens with high SPF always while staying on the sun does not allow one to obtain a proper vitamin D status.